EDUKASI PERILAKU HIDUP BERSIH DAN SEHAT TERHADAP ANAK USIA SEKOLAH DENGAN MEDIA ULAR TANGGA DI SMP METHODIST 1 KUTALIMBARU KABUPATEN DELI SERDANG - Azhary, Muhammad Rifqi; Amirah, Nada; Sitio, Sri Sudewi Pratiwi; Tanjung, Lina Febriani; Putri, Rizqi Nanda; Damanik, Yunita Syahputri (INSTITUT KESEHATAN DELI HUSADA, 2023)
Good hygiene practices (PHBS) are activities that must be carried out by all groups, not only for children during their toddler years, the golden period of growth, but also for middle school children at their peak. And the development of high school students often face health problems including infections due to cat bites due to not practicing PHBS. Therefore, this community service was carried out at Kutalimbaru Methodist 1 Middle School to provide PHBS education to school children using the game Snakes and Ladders as a learning tool. This activity is not just a game of snakes and ladders: students learn while playing. PHBS material is presented through a quiz where participants click on certain numbers and images related to their school's PHBS logo. The launch of the training went well, and in the initial discussions about the game, the students were very enthusiastic and gave a strong response. The application of Hygiene and Sanitation Tips (PHBS) using Snakes and Ladders Media is considered effective in increasing students' awareness and understanding of clean and healthy living behavior. Keywords: Clean and healthy living behavior (PHBS), Education, Snake and Ladder Game